Short-term Efficacy of Hand-Arm Bimanual Intensive Training on Upper Arm Function in Acute Stroke Patients: A Randomized Controlled Trial - Meng, Guilin; Meng, Xiuling; Tan, Yan; Yu, Jia; Jin, Aiping; Zhao, Yanxin; Liu, Xueyuan (Frontiers in Neurology, 2018)
Background: Rehabilitation training during the acute phase of stroke (<48 h) markedly improves movement function of the impaired upper limb. Hand-arm bimanual intensive therapy (HABIT) represents a bimanual intervention that promotes improvements in upper extremity function in children with cerebral palsy. This study repurposed HABIT in acute stroke patients, and assessed recovery of upper extremity function as compared with a conventional rehabilitation program (CRP). Methods: In a randomized trial, 128 patients with acute stroke were assigned to the HABIT or the CRP groups. The primary endpoint was the clinical motor functional assessment that was guided by the Fugl-Meyer motor assessment (FMA), and action research arm test (ARAT) outcomes. The secondary endpoint was an improved neurophysiological evaluation according to the motor-evoked potential amplitude (AMP), resting motion threshold (RMT), and central motor conduction time (CMCT) scores over the 2-week course of therapy. In both groups, scores were evaluated at baseline, 1 week from commencing therapy, and post-therapy. Results: After 2 weeks, the HABIT group showed improved scores compared to the CRP group for FMA (51.7 ± 6.44 vs. 43.5 ± 5.6, P<0.001), ARAT (34.5 ± 6.2 vs. 33.3 ± 6.3, P=0.022), and AMP (1.1 ± 0.1 vs. 1.0 ± 0.1, P<0.001). However, CMCT (8.6 ± 1.0 vs. 9.1 ± 0.6, P=0.054) and RMT (55.3 ± 4.2 vs. 57.5 ± 4.1, P=0.088) were similar between groups. Conclusions: HABIT significantly improved motor functional and neuro- physiological outcomes in patients with acute stroke, which suggested that HABIT represented an improved therapeutic strategy as compared CRP.